Analisis Komparatif Praktik Akuntansi di Iran dan Indonesia - Natalis Christian; Arlina Arlina; Julie Tryany; Vera Laurence Liang; Yohanis Rerung (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Globalization has driven increasingly international economic integration, pushing countries to adjust their accounting standards. This study compares the accounting practices of Iran and Indonesia through a qualitative analysis of academic literature, accounting regulations, and corporate financial reports considering the different cultural, economic, and legal contexts in the two countries. The research results show that Indonesia adopts Financial Accounting Standards (SAK) which are based on IFRS while Iran uses National Accounting Standards which are adapted from IFRS with modifications according to the local context. IFRS adoption in Indonesia is said to be more advanced and closer than Iran because Iran is facing challenges that affect the country's economy, such as US international sanctions. These differences are also influenced by factors such as legal, cultural and social. Despite the differences, both countries show serious efforts in adapting accounting practices to international standards. Overall, this study provides in-depth insights for accounting practitioners, regulators and policy makers to develop better accounting practices in accordance with the needs of each country in an ever-evolving global context.